Vitiligo after borderline lepromatous leprosy: common immunological implications - Cecília M. Sequeira; Felipe Cupertino; José M. Cunha; Maria L. Wan-Del Rey (Sociedade Portuguesa de Dermatologia e Venereologia, 2024)
Objective: The objective of this study is to demonstrate the occurrence of vitiligo after multibacillary (MB) leprosy. Methods: This study was a review of medical registry of patients followed at the leprosy and vitiligo outpatient clinics at a reference university hospital in the city of Rio de Janeiro. Results: Five cases of vitiligo were identified in patients from the MB leprosy, all reactional (before, during, and after treatment), with lesions appearing on average 10 years after the diagnosis of leprosy. Conclusion: There are few reports on the association between the two diseases in the world literature. However, all existing studies to date have shown the predominance of vitiligo in the MB pole. Humoral, innate, and adaptive immunity play an important role in the pathophysiology of MB pole, leprosy reactions, and vitiligo, but they have not yet been fully elucidated. Genome-wide association studies have highlighted several susceptibility genes that also require better understanding.